What is the motor vehicle crash risk for drivers with epilepsy? A systematic review. (December 2021) - Koppel, Sjaan; Di Stefano, Marilyn; Dimech-Betancourt, Bleydy; Aburumman, Mohammed; Osborne, Rachel; Peiris, Sujanie; Williams, Gabrielle; McInnes, Aaron; Stephens, Amanda; Odell, Morris; Darzins, Peteris; Carney, Patrick; et al.
Abstract : Objectives: To establish the crash risk for drivers with epilepsy and quantify any impacts on on-road driving performance. Methods: A systematic search of public health-, psychology-, and transport-databases was conducted. This systematic review was registered with PROSPERO (see CRD42019129664). The quality of evidence for each study was rated using the National Heart, Lung and Blood Institute Quality Assessment tools. Results: Twenty-three studies using various designs published between 1961 and 2017 met the inclusion criteria (n = 18 rated 'good' or 'fair'). Of these 18 studies, only 11 (case-control: n = 2; cohort: n = 8; cross-sectional: n = 1) specifically addressed crash risk for drivers with epilepsy, with five reporting evidence for increased crash risk, (n = 3 rated 'good), three reporting evidence no difference in crash risk relative to controls (n = 2 rated 'good'), and three reporting inconclusive evidence (n = 1 rated 'good'. The remaining seven studies examined crash responsibility, injury severity, anti epileptic medicine, seizure-free intervals, and the influence of auras for drivers with epilepsy. No studies investigated the impacts of epilepsy on on-road driving performance. Significance: There is evidence for a slight elevation of risk for drivers with epilepsy. Generalisability is limited by lack of controlling for confounds and wide time period over which medical treatment and licensing authority requirements applied. Development of consensus based medical and licensing standards taking these findings into account. Highlights: A systematic review was conducted to establish the crash risk for drivers with epilepsy (DWE). 23 studies met the inclusion criteria, with only five published in the last decade. 11 studies explored the crash risk for DWE; (5 = increased risk, 3 = no difference, 3 = inconclusive evidence. Evidence suggests a slight elevation of crash risk for DWE. Development of consensus based medical and licensing standards and encouraging case by case application should be considered.